Silica Induction of Diverse Inflammatory Proteome in Lungs of Lupus-Prone Mice Quelled by Dietary Docosahexaenoic Acid Supplementation - Rajasinghe, Lichchavi D.; Bates, Melissa A.; Benninghoff, Abby D.; Wierenga, Kathryn A.; Harkema, Jack R.; Pestka, James J. (Frontiers in Immunology, 2022)
Repeated short-term intranasal instillation of lupus-prone mice with crystalline silica (cSiO2) induces inflammatory gene expression and ectopic lymphoid neogenesis in the lung, leading to early onset of systemic autoimmunity and rapid progression to glomerulonephritis. These responses are suppressed by dietary supplementation with the ω-3 polyunsaturated fatty acid docosahexaenoic acid (DHA). Here, we tested the hypothesis that dietary DHA supplementation suppresses cSiO2-induced inflammatory proteins in bronchoalveolar alveolar lavage fluid (BALF) and plasma of lupus-prone mice. Archived tissue fluid samples were used from a prior investigation in which 6 wk-old lupus-prone female NZBWF1 mice were fed isocaloric diets containing 0 or 10 g/kg DHA for 2 wk and then intranasally instilled with 1 mg cSiO2 or vehicle once weekly for 4 wks. Cohorts were terminated at 1, 5, 9 or 13 wk post-instillation (PI). BALF and plasma from each cohort were analyzed by high density multiplex array profiling of 200 inflammatory proteins. cSiO2 time-dependently induced increases in the BALF protein signatures that were highly reflective of unresolved lung inflammation, although responses in the plasma were much less robust. Induced proteins in BALF included chemokines (e.g., MIP-2, MCP-5), enzymes (e.g., MMP-10, granzyme B), adhesion molecules (e.g., sE-selectin, sVCAM-1), co-stimulatory molecules (e.g., sCD40L, sCD48), TNF superfamily proteins (e.g., sTNFRI, sBAFF-R), growth factors (e.g., IGF-1, IGFBP-3), and signal transduction proteins (e.g., MFG-E8, FcgRIIB) - many of which were blocked or delayed by DHA supplementation. The BALF inflammatory proteome correlated positively with prior measurements of gene expression, pulmonary ectopic lymphoid neogenesis, and induction of autoantibodies in the lungs of the control and treatment groups. Ingenuity Pathway Analysis (IPA) revealed that IL-1β, TNF-α, and IL-6 were among the top upstream regulators of the cSiO2-induced protein response. Furthermore, DHA’s effects were associated with downregulation of cSiO2-induced pathways involving i) inhibition of ARE‐mediated mRNA decay, ii) bacterial and viral pattern recognition receptor activation, or iii) TREM1, STAT3, NF-κB, and VEGF signaling and with upregulation of PPAR, LXR/RXR and PPARα/RXRα signaling. Altogether, these preclinical findings further support the contention that dietary DHA supplementation could be applicable as an intervention against inflammation-driven autoimmune triggering by cSiO2 or potentially other environmental agents.